Geotechnical Characteristics of Subsoil for Different Sectors of Islamabad - Moeen-ul din; Jamal Ali; Abdul Qudoos Khan; Farjad Sami (NUST Journal of Engineering Sciences, 2019)
Geotechnical site investigations are essential in determining subsoil stratigraphy and soil strength and is considered mandatory for design of foundations.  This study presents the generalized profiles for subsurface stratigraphy and insitu soil strength (average SPT N values) for different sectors of Islamabad on the basis of wide-ranging experimental work carried out by several agencies in fieldand laboratory testing carried out at the number of locations in the study area. Data from 208 geotechnical site investigations of Islamabad have been collected and subsurface profiling for those sectors is carried out that had more than four data points. The experimental data of the study area has shown potential for development of profile map for 11 different sectors of Islamabad using data of 144 geotechnical site investigations. Generalized soil profile and average SPT N values for each sector have been generated to a depth of 7m which is considered sufficient for lightly loaded structures with shallow foundations. Average SPT N value profile coupled with soil stratigraphy for each zone is established that can used to determine shear strength parameters and bearing capacity of soil using SPT based empirical correlations. The generalized soil profiles will be helpful during feasibility study and planning geotechnical site investigations for mega projects and can also be used to determine engineering properties of subsoil for small scale projects.